Inclusive Approaches in Historic Green Spaces - Sikora, Dorota (Protection of Cultural Heritage, 2022)
In line with the ideas of sustainable development contained in the UN resolution "Transforming our world: The 2030 Agenda for Sustainable Development", the key objectives to be achieved by 2030 include: ensuring universal access to green spaces and public spaces that are safe for all and inclusive, while at the same time strengthening efforts to protect cultural and natural heritage. The article presents, using selected examples of historic parks, gardens and landscapes, how these goals are being realised. The subjects of the study were in particular: The Garden of Versailles, Stonehenge and the cultural landscape surrounding this monument, managed by English Heritage and Historic England’s policy of making historic parks, gardens and landscapes accessible. The analysis of the strategies for making historic green spaces and cultural landscapes accessible to people with special needs, developed by the institutions mentioned above, has allowed to conclude the article with proposals of general principles for an inclusive policy towards this group of monuments.